2010
DOI: 10.1016/j.bpj.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy and Persistence Length Analysis of Semi-Rigid Smooth Muscle Tropomyosin Strands

Abstract: The structural mechanics of tropomyosin are essential determinants of its affinity and positioning on F-actin. Thus, tissue-specific differences among tropomyosin isoforms may influence both access of actin-binding proteins along the actin filaments and the cooperativity of actin-myosin interactions. Here, 40 nm long smooth and striated muscle tropomyosin molecules were rotary-shadowed and compared by means of electron microscopy. Electron microscopy shows that striated muscle tropomyosin primarily consists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 40 publications
4
47
0
Order By: Relevance
“…For the WT Tpm, we obtained a PL of 877 Å which is a little less than the value obtained for actin-free Tpm [*1000 Å , see Li et al (2010b) and Sousa et al (2010)], suggesting the Tpm is more curved upon binding to F-actin. For both WT and Tpm mutants, we found moderate correlation between PL and RMSF h i Tpm or RMSF h i FÀactin (with Pearson correlation = -0.5), which is consistent with the idea that the PL not only depends on flexibility but also on the end-to-end curvedness of Tpm (Li et al 2010b).…”
Section: Global Flexibility Analysis Of Tpm On F-actinmentioning
confidence: 81%
See 1 more Smart Citation
“…For the WT Tpm, we obtained a PL of 877 Å which is a little less than the value obtained for actin-free Tpm [*1000 Å , see Li et al (2010b) and Sousa et al (2010)], suggesting the Tpm is more curved upon binding to F-actin. For both WT and Tpm mutants, we found moderate correlation between PL and RMSF h i Tpm or RMSF h i FÀactin (with Pearson correlation = -0.5), which is consistent with the idea that the PL not only depends on flexibility but also on the end-to-end curvedness of Tpm (Li et al 2010b).…”
Section: Global Flexibility Analysis Of Tpm On F-actinmentioning
confidence: 81%
“…To complement the RMSF analysis and compare with other studies of Tpm flexibility (Li et al 2010a(Li et al , b, c, 2012Loong et al 2012a, b;Sousa et al 2010), we have calculated the apparent persistent length (PL) with the commonly used tangent correlation method (also used in previous studies, see (Li et al 2010b;Loong et al 2012b)) for the WT and Tpm mutants (see Table 1). For the WT Tpm, we obtained a PL of 877 Å which is a little less than the value obtained for actin-free Tpm [*1000 Å , see Li et al (2010b) and Sousa et al (2010)], suggesting the Tpm is more curved upon binding to F-actin.…”
Section: Global Flexibility Analysis Of Tpm On F-actinmentioning
confidence: 99%
“…Li et al found that the tropomyosin coiled-coil is rather stiff with a persistence length about 12 times its own length (108,(134)(135)(136)(137)199). Thus, local troponin-and myosininduced shifts of semirigid tropomyosin on the actin filament can be expected to be propagated along the tropomyosin cable with limited decrement, producing expected filament cooperative effects.…”
Section: Gestalt Binding Of Tropomyosin On F-actinmentioning
confidence: 92%
“…The very small persistence length of the 10 nm diameter IF containing many coiled-coil dimer subunits per cross-section is surprising since the persistence length of a single coiled-coil dimer such as tropomyosin is itself approximately 100 nm. [20]. The thinner, semiflexible F-actin is an order of magnitude stiffer than IFs and has a persistence length ranging from 3–17 um [21], which is comparable to the typical filament length.…”
Section: Mechanical Properties Of Individual Cytoskeletal Filamentsmentioning
confidence: 99%